Characterization of airborne BTEX exposures during use of lawnmowers and trimmers. Issue 4 (4th July 2019) - Avens, Heather J.; Maskrey, Joshua R.; Insley, Allison L.; Unice, Kenneth M.; Reid, Rachel C. D.; Sahmel, Jennifer
ABSTRACT: Few studies have evaluated airborne exposures to benzene, toluene, ethylbenzene, and xylenes (BTEX) during operation of two-stroke and four-stroke small engines, such as those in lawn maintenance equipment. Full-shift, 8-hour personal samples were collected during a simulation study to characterize yard maintenance activities including mowing, trimming, and fueling. Short-term, 15-minute personal samples were collected to separately evaluate mowing and trimming exposures. Mean 8-hour time weighted average (TWA) BTEX concentrations were 2.3, 5.8, 0.91, and 4.6 ppb, respectively (n = 2). Mean 15-minute TWA BTEX concentrations were 1.6, 1.8, 0.22, and 1.3 ppb, respectively, during mowing and 1.2, 3.6, 0.68, and 3.3 ppb, respectively, during trimming (n = 3 per task). Measured BTEX concentrations during fueling were 20–110, 61–310, 8–41, and 40–203 ppb, respectively (n = 2, duration 2–3 minutes). These exposure concentrations were well below applicable US occupational exposure limits.